Determination of Molecular Weight and Viscosity of Irradiated Polystyrene (Baghdad Science Journal, 2023)
The varied applications of polystyrene in various fields of life led to examining the cause of radiation influence on some rheological behavior of commercial Polystyrene (PS) solution in the chloroform (CHCl3) solvent. Polystyrene grains shape samples were irradiated using the radioactive element Cesium- 137 with (9 µci) activity for 10, 20, and 30 minutes. The viscosity of the polymer solution depends on the concentration and size (i.e. molecular weight) of the dissolved polymer. Experimental data showed that the radiation dose affected the value of viscosity (shear, relative, specific, and reduced). The viscosity value significantly reduced at 10 min radiation dose and when increasing the dose, the viscosity value increased up to 30 minutes. Deterioration of the polymer structure was recorded for a 10 minutes radiation dose. With the increase of radiation time, which reached 30 minutes, cross-linking was performed due to the substance gaining additional doses of radiation. The molecular weight of polystyrene increased with the increase of irradiation time, but no value was recorded for a molecular weight higher than 56089, which is for not irradiated polystyrene. The study concluded that the radiation dose is able to control the chemical composition of the polymer, therefore the behavior of the polymer in the solvent is determined by the radiation dose to which it is exposed.